Age-related atrial fibrosis. - Gramley, F; Lorenzen, J; Knackstedt, C; Rana, O; Saygili, E; Frechen, D; Stanzel, S; Pezzella, F; Koellensperger, E; Weiss, C; Münzel, T; Schauerte, P (2009)
Many age-related diseases are associated with, and may be promoted by, cardiac fibrosis. Transforming growth factor (TGF)-beta, hypoxia-induced factor (HIF), and the matrix metalloproteinase (MMP) system have been implicated in fibrogenesis. Thus, we investigated whether age is related to these systems and to atrial fibrosis. Right atrial appendages (RAA) obtained during heart surgery (n = 115) were grouped according to patients' age (<50 years, 51-60 years, 61-70 years, or >70 years). Echocardiographic ejection fractions (EF) and fibrosis using Sirius-red-stained histological sections were determined. TGF-beta was determined by quantitative RT-PCR and hypoxia-related factors [HIF1 alpha, the vascular endothelial growth factor (VEGF)-receptor, CD34 (a surrogate marker for microvessel density), the factor inhibiting HIF (FIH), and prolyl hydroxylase 3 (PHD 3)] were detected by immunostaining. MMP-2 and -9 activity were determined zymographically, and mRNA levels of their common tissue inhibitor TIMP-1 were determined by RT-PCR. Younger patients (<50 years) had significantly less fibrosis (10.1% +/- 4.4% vs 16.6% +/- 8.3%) than older individuals (>70 years). While HIF1 alpha, FIH, the VEGF-receptor, and CD34 were significantly elevated in the young, TGF-beta and PHD3 were suppressed in these patients. MMP-2 and -9 activity was found to be higher while TIMP-1 levels were lower in older patients. Statistical analysis proved age to be the only factor influencing fibrogenesis. With increasing age, RAAs develop significantly more fibrosis. An increase of fibrotic and decrease of hypoxic signalling and microvessel density, coupled with differential expression of MMPs and TIMP-1 favouring fibrosis may have helped promote atrial fibrogenesis.